Contributing Factors toward the Participation of Education Equality Program Learners - Nugroho, Rivo; Rahma, Rezka Arina; Yulianingsih, Wiwin (Journal of Nonformal Education, 2018)
Success of Learners in learning is determined strongly by the learners themselves. One factor that determines the success is the existence of learning participation of the learners themselves. In non-formal education,  learning participation is an  inseparable part of the circuit of  the learning. This research is aimed to review what factors that contributed to the learning participation of the learners of Package B (National Junior High School Equivalency) Equality Learning Program in SKB (District Technical Office for Early Childhood, Nonformal and Informal Education) Gresik. Method used to conduct the research is qualitative approach. In SKB Gresik as place of the research, the researcher use several informants  for data exploration, by using interview, observation, questionnaire , and documentation of  package B   Equality Education Program as a way to explore data. Data obtained, then, analyzed by  data collection procedure, data reduction , data presentation, data interpretation, and data conclusion. The result of the research show that learners participation in package B equality program  in SKB Gresik are tangible in three forms, that are: (a) participation in planning stage, (b) participation in executing stage, (c) participation in evaluation stage. Then, factor that influence participation of  learners are consists of internal and external factors. Internal factors include physical condition such as health, age, functioning of five sense, and psychological condition of the learners themselves. Then external factors include the education level of the parents, socio-economical condition of the family, educator’s competence,  and learning method used in learning process.